Integrating Neuroscience Into Counseling Psychology: A Systematic Review of Current Literature. (August 2016) - Goss, David
A systematic review was carried out to investigate what themes current academic journal publications discuss in relation to the integration of neuroscience into counseling psychology. After initial database searches, a thematic analysis was performed on the available literature, determining the key themes and subjects of discussion across the data. A total of 21 publications were carried through to synthesis, with four main themes emerging: Biopsychosocial Topics of Discussion, Neuroscience Education, Integrating Neuropsychology, and Implications of Integration. Further subthemes are discussed, providing a richer description of the publication content focus. There is currently a small body of literature associated with this paradigm. However, the literature available provides evidence of a number of topic areas in which neuroscience can be integrated into counseling psychology. Recent publications may signal a reawakening of an earlier interest in the paradigm.